2017
DOI: 10.1002/jnm.2278
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic and thermal analysis of underground power solid‐conductor cables under harmonic and unbalancing currents based on FEM

Abstract: In this paper, electromagnetic and thermal analyses are performed on underground power solid-conductor cables under harmonic and unbalancing currents. The loss, life time, and produced magnetic field are calculated. Different balanced and unbalance load currents and also sinusoidal and harmonic profiles are considered. Moreover, the effects of different distances between cables are analyzed. Power cable losses and produced magnetic fields around power cables are computed based on electromagnetic analysis by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In addition, in the study of Al-Saud [13], the FEM-PSO method was used to optimize the three-core cable cross-sections, and the optimum dimensions were obtained. Rasoulpoor et al [14] had studied the heat transfer characteristics for buried cables with unbalanced current by using FEM method. In their study, the heat source produced by the cable was coupled and it was found that the cables arranged in parallel form would have longer working life.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the study of Al-Saud [13], the FEM-PSO method was used to optimize the three-core cable cross-sections, and the optimum dimensions were obtained. Rasoulpoor et al [14] had studied the heat transfer characteristics for buried cables with unbalanced current by using FEM method. In their study, the heat source produced by the cable was coupled and it was found that the cables arranged in parallel form would have longer working life.…”
Section: Introductionmentioning
confidence: 99%
“…The second application is for a circular cross-section of a high voltage insulated steel armoured electrical cable. The steel armour, that is used to provide sustenance for the high voltage electrical cables to endure mechanical stress as they are buried underground, also traps electromagnetic disturbances occurring inside the cable due to current imbalances and material defects [51]. The solution of the wave equation inside these geometries provides the distribution of the electromagnetic energy within the material, which then could be coupled with the diffusion equation to analyse various thermal properties [52,53].…”
Section: Example Of Resonant Cavitymentioning
confidence: 99%
“…The one-dimensional (1D) network was adopted for the cable temperature estimation [11][12][13], whereas in the case of cable joint, a 2D RC analogue was normally chosen with the subdivision of the joint into a number of elemental cylindrical volumes, and the effectiveness of the thermal network was validated by the temperature-rise test [14,15]. With the improvement of mesh generation and post-processing capabilities, FEM has been widely used in the thermophysics and heat engineering [16][17][18][19][20]. By using transient FEM for thermal analysis, the hot spot temperature rise of 110 kV cable joint has been calculated within an acceptable error range [21].…”
Section: Introductionmentioning
confidence: 99%